Ischemic Volkmann Contracture From Intrauterine Compartment Syndrome. Issue 2 (June 2022) - Vandenheuvel, Julia; Teixeira, Robert; Song, Ethan; Kozin, Scott; Davis, Wellington; Rice, Scott
Neonatal compartment syndrome also known as congenital Volkmann ischemic contracture is a rare condition with limited cases described in literature. This condition presents with progressive limb ischemia and tissue necrosis at birth or immediately thereafter. It often involves the upper extremity with cutaneous lesions that can be mistaken for other entities. Failure to recognize the sentinel lesion with underlying deeper pathology (compartment syndrome) can result in delayed treatment and long-term functional impairment. We report a newborn at birth with unilateral, well-demarcated areas of ulceration on the forearm and antecubital fossa with functional impairment including wrist drop and absence of finger flexion.